PERAN KOMUNIKASI INTERPERSONAL ORANG TUA DAN GURU SISWA SLB (SEKOLAH LUAR BIASA) DALAM PEMBELAJARAN DARING SELAMA PANDEMI COVID – 19 - Imarotussolikhah Imarotussolikhah; Puri Kusuma Dwi Putri (STKIP PGRI Situbondo, 2023)
The education system in Indonesia has been severely affected by the Covid-19 pandemic. The transition to the face-to-face school learning system was carried out by the internet to prevent the spread of the virus that causes Covid-19, including SLB Empat Lima Babat. This online learning has obstacles for parents and teachers of students with special needs (ABK), where obstacles can occur when communication is not conveyed properly. It's important to provide additional help and supervision to those around children with special needs as they grow older, and in the school environment, teachers, students, and parents need to have interpersonal communication in educational activities. Despite the widespread damage caused by the Covid-19 outbreak, schools had to keep running. This research using social penetration theory will reveal the side of depth (depth) and breatdh (breadth), qualitative descriptive research methods to find out a complete picture of certain individuals or groups about a symptom that is occurring. The informants consisted of 3 teachers and 3 parents of SLB Empat Lima students. The results of this study found that the learning method during the Covid-19 pandemic used online and offline methods. Online using the Whatsaap application, Zoom, Google Meet, and others. Other findings found 3 problems/difficulties experienced by parents and teachers during covid-19 learning, namely, children cannot be managed and lazy to learn, parents do not respond to teachers, and parents have difficulty understanding teacher material.